Music and Digital Media A planetary anthropology - Born, Georgina (UCL Press, 2022)
Anthropology has neglected the study of music. Music and Digital Media shows how and why this should be redressed. It does so by enabling music to expand the horizons of digital anthropology, demonstrating how the field can build interdisciplinary links to music and sound studies, digital/media studies, and science and technology studies. Music and Digital Media is the first comparative ethnographic study of the impact of digital media on music worldwide. It offers a radical and lucid new theoretical framework for understanding digital media through music, showing that music is today where the promises and problems of the digital assume clamouring audibility. The book contains ten chapters, eight of which present comprehensive original ethnographies; they are bookended by an authoritative introduction and a comparative postlude. Five chapters address popular, folk, art and crossover musics in the global South and North, including Kenya, Argentina, India, Canada and the UK. Three chapters bring the digital experimentally to the fore, presenting pioneering ethnographies of anextra-legal peer-to-peer site and the streaming platform Spotify, a series of prominent internet-mediated music genres, and the first ethnography of a global software package, the interactive music platform Max. The book is unique in bringing ethnographic research on popular, folk, art and crossover musics from the global North and South into a comparative framework on a large scale, and creates an innovative new paradigm for comparative anthropology. It shows how music enlarges anthropology while demanding to be understood with reference to classic themes of anthropological theory. Praise for Music and Digital Media 'Music and Digital Media is a groundbreaking update to our understandings of sound, media, digitization, and music. Truly transdisciplinary and transnational in scope, it innovates methodologically through new models for collaboration, multi-sited ethnography, and comparative work. It also offers an important defense of-and advancement of-theories of mediation.' Jonathan Sterne, Communication Studies and Art History, McGill University 'Music and Digital Media is a nuanced exploration of the burgeoning digital music scene across both the global North and the global South. Ethnographically rich and theoretically sophisticated, this collection will become the new standard for this field.' Anna Tsing, Anthropology, University of California at Santa Cruz 'The global drama of music's digitisation elicits extreme responses - from catastrophe to piratical opportunism - but between them lie more nuanced perspectives. This timely, absolutely necessary collection applies anthropological understanding to a deliriously immersive field, bringing welcome clarity to complex processes whose impact is felt far beyond what we call music.' David Toop, London College of Communication, musician and writer 'Spanning continents and academic disciplines, the rich ethnographies contained in Music and Digital Media makes it obligatory reading for anyone wishing to understand the complex, contradictory, and momentous effects that digitization is having on musical cultures.' Eric Drott, Music, University of Texas, Austin 'This superb collection, with an authoritative overview as its introduction, represents the state of the art in studies of the digitalisation of music. It is also a testament to what anthropology at its reflexive best can offer the rest of the social sciences and humanities.' David Hesmondhalgh, Media and Communication, University of Leeds 'This exciting volume forges new ground in the study of local conditions, institutions, and sounds of digital music in the Global South and North. The book's planetary scope and its commitment to the "messiness" of ethnographic sites and concepts amplifies emergent configurations and meanings of music, the digital, and the aesthetic.' Marina Peterson, Anthropology, University of Texas, Austin